Quantitative Assessment of Unemployment among Youths in Malaysia - Lok, Lee Wen; Misiran, Masnita; Sapiri, Hasimah; Supadi, Siti Suzlin; Md Yusof, Zahayu (Penerbit UTM Press, 2022)
The youth unemployment rate is three times greater than the total unemployment rate in Malaysia, also it is moving more fluctuated and growing every year after a significant rise in 2015. Hence this study aims to determine the relationship between the influential factors and the youth unemployment rate and to examine which factors can serve as future indicators of youth unemployment rate in Malaysia. The annual basis of secondary data from 1992 to 2019 and the analysis methods are used Pearson correlation and multiple linear regression. The correlation results show that inflation rate, trade openness and urbanization are negatively correlated with youth unemployment rate, while Foreign Direct Investment (FDI), migration and exchange rate are positively correlated. Also, the regression results indicate only four factors which are FDI, trade openness, exchange rate, and urbanization are significant to the youth unemployment rate. Thus, they can serve as the future indicators of youth unemployment rate in Malaysia. More specifically, FDI and exchange rate are positively significant correlated with youth unemployment rate, whereas trade openness and urbanization are negatively significant related with youth unemployment rate